2022
DOI: 10.1007/s40843-022-2105-6
|View full text |Cite
|
Sign up to set email alerts
|

Interface interaction-mediated design of tough and conductive MXene-composited polymer hydrogel with high stretchability and low hysteresis for high-performance multiple sensing

Abstract: Conductive hydrogels based on two-dimensional (2D) nanomaterials, MXene, have emerged as promising materials for flexible wearable sensors. In these applications, the integration of high toughness, ultrastretchability, low hysteresis, self-adhesiveness, and multiple sensory functions into one gel is essential. However, serious issues, such as easy restacking and inevitable oxidation of MXene nanosheets in aqueous media and weak interfacial bindings between MXene and the gel network, make it almost impossible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Compared to the recently reported stretchable hydrogels, the PAM–HA–Zn1.0 hydrogel possessed higher breaking elongation and toughness (Table S2†). 9,33–41…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the recently reported stretchable hydrogels, the PAM–HA–Zn1.0 hydrogel possessed higher breaking elongation and toughness (Table S2†). 9,33–41…”
Section: Resultsmentioning
confidence: 99%
“…The conductivity of the hydrogels was measured at ambient temperature with an electrochemical workstation (CHI760E, CH Instruments, China) by the alternating current impedance method. 9 The real-time electric resistance change of the hybrid hydrogel caused by the external force was recorded by using the same electrochemical workstation. The relative resistance change (RRC) and the gauge factor (GF) of the hydrogel were calculated individually as:RRC = ( R − R 0 )/ R 0 GF = ( R − R 0 )/( ε × R 0 )where R 0 is the initial resistance at the strain value of 0, and R is the dynamic resistance at a strain value of ε during measurement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tifeng Jiao et al found that by adding gelatin-modified MXene to the Polyacrylamide (PAAm) hydrogel, the tensile strength increased significantly (1100%) and the tensile strength increased significantly (430 kPa). [ 12 ]. Up to now, there have been few studies of all-solid supercapacitors based on ionic liquid gel electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of nanotechnology, nanocomposites and nanostructures have attracted significant attention due to their unique physical and chemical properties and variable functionalities [ 1 , 2 , 3 ]. Both the various compositions and the construction process of nanostructured composites influence their performances, with application areas ranging from new chemical reactions, organic semiconductors, photovoltaic technology, and photocatalysts to biosensors and energy materials [ 4 , 5 , 6 ].…”
mentioning
confidence: 99%